Implementasi Model Pembelajaran Self Organized Learning Environments Berbasis Tri Kaya Parisudha untuk Meningkatkan Hasil Belajar Mahasiswa - Ni Nyoman Kurnia Wati (Edukasi: Jurnal Pendidikan Dasar, 2021)
This study aims to improve learning outcomes of IPS 1 subject to PGSD Class A at STAHN Mpu Kuturan Singaraja through the implementation of the SOLE Learning Model based on Tri Kaya Parisudha. Based on the results of data analysis, it can be concluded that the implementation of the SOLE learning model based on Tri Kaya Parisudha can improve the learning outcomes of IPS 1 Elementary School Subjects in PGSD class A 3rd semester students at STAHN Mpu Kuturan Singaraja. This result is evident from the increase in the average increase in cycle I from 82 to 87 in cycle II. Students' classical completeness also increased from 83% in cycle I to 94% in cycle II. Keywords: SOLE model, Tri Kaya Parisudha, learning outcomes